Spontaneous pneumomediastinum in children with viral infections: report of three cases related to rhinovirus or respiratory syncytial virus infection : case report - Leinert, Johanna; Perez Ortiz, Alba; Rafat, Neysan (Children, 2022)
Background: Spontaneous pneumomediastinum (SP) is generally a benign condition which can have various etiologies. Data on SP related to respiratory viral infections in children are rare and there are currently no official guidelines or consistent treatment recommendations for these patients. Aim: To discuss treatment options considering the recommendations for SP with different etiologies. Methods: We report three cases of SP, which were related to rhinovirus or respiratory syncytial virus (RSV) infection. Results: All three patients presented with typical symptoms of a respiratory tract infection and required oxygen supplementation during the hospital stay. All children benefited from a conservative, supportive therapy, and bed rest, and could be discharged after seven days or less without remaining symptoms. Conclusion: Surveillance and monitoring might be reasonable to detect and treat potential complications in children with SP due to viral infections, as one child developed an increasing pneumothorax, which had to be treated with a thoracic drainage.